PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TEAM ASSISTED INDIVIDUALIZATION (TAI) DALAM MENINGKATKAN HASIL BELAJAR TENTANG FUNGSI KOMPOSISI DAN FUNGSI INVERS PADA PESERTA DIDIK KELAS XI ILMU SOSIAL - 1 SEMESTER 2 SMA NEGERI MAGEPANDA TAHUN PELAJARAN 2019/202 - FALENTINUS PIO (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The problem raised in this research is whether the Team Assisted Individualized (TAI) cooperative learning model can improve learning outcomes and students' understanding of concept X Class IIS1 Magepanda High School on Composition and Inverse Functions. This study aims to determine the increase in understanding of students of class X IIS1 in Magepanda Public High School in learning mathematics through the cooperative learning model of Assisted Individualized (TAI) learning. This study describes the design and implementation of Team Assisted Individualized (TAI) cooperative learning in improving learning outcomes and conceptual understanding of the Composition Function in Magepanda Public High School. This research is a classroom action research that occurred in two cycles. The research subjects used in this study were students of class X IIS 1 in the even semester of the 2019/2020 school year. There were 36 people consisting of 18 men and 18 women. in the form of learning outcomes and understanding of students' learning concepts. The results of the study show that Team Assisted Individualized (TAI) cooperative learning can improve learning outcomes and understanding mathematical concepts about composition and inverse functions. Student learning outcomes increase from cycle to cycle, as well as participant responses students towards Team Assisted Individualized (TAI) cooperative learning are very positive.